2019
DOI: 10.1177/1535759719854753
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Residue of Epilepsy Surgery: De Novo or Not

Abstract: [Box: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The reported incidence of de novo psychosis after epilepsy surgery varies depending on the studies. In one study of a cohort of 106 patients who underwent resective surgery for intractable epilepsy [7], 88% of patients suffered from temporal lobe seizures. The authors reported a rate of 6% of de novo psychosis after epilepsy surgery, and identified that psychiatric complications occurred more frequently in multi‐lobar epileptic foci and in patients undergoing deep brain stimulation of the anterior nuclei of the thalamus.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of de novo psychosis after epilepsy surgery varies depending on the studies. In one study of a cohort of 106 patients who underwent resective surgery for intractable epilepsy [7], 88% of patients suffered from temporal lobe seizures. The authors reported a rate of 6% of de novo psychosis after epilepsy surgery, and identified that psychiatric complications occurred more frequently in multi‐lobar epileptic foci and in patients undergoing deep brain stimulation of the anterior nuclei of the thalamus.…”
Section: Discussionmentioning
confidence: 99%